Perancangan Ulang Fasilitas Dan Ruang Produksi Untuk Meningkatkan Output Produksi - Murnawan, Hery; Wati, Putu Eka Dewi Karunia (Jurnal Teknik Industri, 2018)
This research discusses the redesign of facility layout on metal smelting SMEs that experienced changes in the type of products produced due to shifting consumer needs. Changes in the type of product produced affect the flow of the production process and result in decreased productivity. This study aims to redesign facilities adapted to the type of product produced. Re-layout processes using the conventional method is started by making the operation process chart, drawing the initial layout, and calculate the total moment of product using the From-to Chart (FTC). By using some trial obtained a trial layout that can increase the productivity based on the total moment of the product and the number of output that can be produced. This study also determines the Cost of Production (HPP) for all metal casting products and compares them with previous conditions. This study shows that by re-layout, the output will be greater and the cost of production is cheaper.